2012
DOI: 10.1007/s00253-012-4489-y
|View full text |Cite
|
Sign up to set email alerts
|

In vitro propagation and production of cardiotonic glycosides in shoot cultures of Digitalis purpurea L. by elicitation and precursor feeding

Abstract: Digitalis purpurea L. (Scrophulariaceae; Foxglove) is a source of cardiotonic glycosides such as digitoxin and digoxin which are commercially applied in the treatment to strengthen cardiac diffusion and to regulate heart rhythm. This investigation deals with in vitro propagation and elicited production of cardiotonic glycosides digitoxin and digoxin in shoot cultures of D. purpurea L. In vitro germinated seedlings were used as a primary source of explants. Multiple shoot formation was achieved for three explan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
28
2
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 63 publications
7
28
2
2
Order By: Relevance
“…There were numerous reports on precursor feeding strategies in plant cell/organ cultures to improve secondary metabolites production whereas the growth characteristics were considerably reduced upon precursor treatment depending upon the plant species tested. For example, inclusion of cholesterol and squalene in the culture medium confirmed extensive synthesis of digitoxin and digoxin in Digitalis purpurea culture, whereas their addition reduced the biomass accumulation [47]. Addition of mevalonic acid increased production of artemisinin in cell suspension culture of A. annua and its supplementation in the medium reduced the growth properties [38].…”
Section: Discussionmentioning
confidence: 95%
“…There were numerous reports on precursor feeding strategies in plant cell/organ cultures to improve secondary metabolites production whereas the growth characteristics were considerably reduced upon precursor treatment depending upon the plant species tested. For example, inclusion of cholesterol and squalene in the culture medium confirmed extensive synthesis of digitoxin and digoxin in Digitalis purpurea culture, whereas their addition reduced the biomass accumulation [47]. Addition of mevalonic acid increased production of artemisinin in cell suspension culture of A. annua and its supplementation in the medium reduced the growth properties [38].…”
Section: Discussionmentioning
confidence: 95%
“…This could be supported by Patil et al. who noted that the decrease in biomass growth and the raise in the production of digitoxin and digoxin as a result of feeding the precursors in the shoot cultures of Digitalis purpurea .…”
Section: Discussionmentioning
confidence: 80%
“…On the other hand, adding l-arginine on day 20 of the culture (the late exponential growth phase and the early exponential phase for solasodine production) has possibly allowed this precursor to involve fully in the secondary metabolism, producing more solasodine. This could be supported by Patil et al [43] who noted that the decrease in biomass growth and the raise in the production of digitoxin and digoxin as a result of feeding the precursors in the shoot cultures of Digitalis purpurea.…”
Section: The Influence Of the Concentration And Adding Time Of L-argimentioning
confidence: 77%
“…Sivanandhan et al [27] reported that squalene and cholesterol reduced biomass accumulation in Withania somnifera suspension cultures. In another report, it was found that biomass production was decreased due to the addition of squalene and cholesterol in shoot cultures of Digitalis purpurea [12].…”
Section: Effect Of Precursors On Biomass Accumulation In Ddeltoidea mentioning
confidence: 95%